Heels Dance on Social Media: Stripping the Female Body of the Social Norms - Fitriani Marchellita Halim; Jenny Mochtar (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study explores how heels dancers challenge social norms around the female bodyand examines audience reactions along with the dancers' responses. Using Stuart Hall’s encoding/decoding model, the analysis highlights how these dancers employ subversive strategies, framed by Foucault’s counter-conduct, Butler’s gender performativity, and Dolezal’s body shame. Data includes Instagram posts and audience comments from @jessynirmalaa, @heelsnation.id, and @curvescollective.id from August 2021 to July 2024. The findings reveal that the dancers defy norms with brazen costumes, sensual movements, and subversive narratives, eliciting mixed audience reactions ranging from support to resistance. This dynamic interplay reveals the dancers’ bodies as an arena of struggle, challenging and redefining dominant social meanings.